2007
DOI: 10.1002/hipo.20379
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of NMDAR‐independent long‐term potentiation at hippocampal CA1 synapses following early adolescent exposure to chronic intermittent ethanol: Role for sigma‐receptors

Abstract: Adolescent humans who abuse alcohol are more vulnerable than adults to the development of memory impairments. Memory impairments often involve modifications in the ability of hippocampal neurons to establish long-term potentiation (LTP) of excitatory neurotransmission; however, few studies have examined how chronic ethanol exposure during adolescence affects LTP mechanisms in hippocampus. We investigated changes in LTP mechanisms in hippocamal slices from rats exposed to intoxicating concentrations of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 85 publications
7
33
0
Order By: Relevance
“…In contrast, long-term ethanol exposure has been shown to produce upregulation of NMDAR function/expression in the hippocampus (Nelson et al, 2005), amygdala (Roberto et al, 2006), and striatum (Wang et al, 2010), although it is not clear whether this leads to an enhancement of NMDAR-dependent synaptic plasticity (Stephens et al, 2005; Xia et al, 2006; Sabeti and Gruol, 2008). In the present study, we found that VTA dopamine neurons exhibit increased susceptibility to the induction of mGluR/IP 3 -dependent LTP of NMDAR EPSCs after repeated ethanol exposure in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, long-term ethanol exposure has been shown to produce upregulation of NMDAR function/expression in the hippocampus (Nelson et al, 2005), amygdala (Roberto et al, 2006), and striatum (Wang et al, 2010), although it is not clear whether this leads to an enhancement of NMDAR-dependent synaptic plasticity (Stephens et al, 2005; Xia et al, 2006; Sabeti and Gruol, 2008). In the present study, we found that VTA dopamine neurons exhibit increased susceptibility to the induction of mGluR/IP 3 -dependent LTP of NMDAR EPSCs after repeated ethanol exposure in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, this seems inconsistent with the withdrawal-associated hyperactivity of Schaffer collateral-CA1 synapses measured in latter studies (Hendricson et al, 2007; Thomas et al, 1998b). And more recent findings suggest that chronic exposure to a liquid diet or ethanol vapor may actually enhance LTP at CA1 glutamate synapses (Fujii et al, 2008; Sabeti and Gruol, 2008). In fact, the Sabeti and Gruol study found that the effects of chronic ethanol on LTP in this brain region are dependent upon the age of the animal during exposure, with increased LTP expression occurring in younger adolescents (28–36 days old) and decreased LTP expression found in older adolescent animals (45–50 days old).…”
Section: Ethanol Exposure In Vivo and The Plasticity Of Plasticitymentioning
confidence: 99%
“…A high percentage of adolescents experiment with alcohol and alcohol consumption by this population is characterized by heavy or binge drinking (SAMHSA, 2012). These phenomena are of particular concern because neuronal plasticity, synaptic remodeling, neurotransmission, and neurogenesis are highly active, alcohol-sensitive processes in the adolescent brain as demonstrated in animal models (Carpenter-Hyland and Chandler, 2007; Crews and Nixon, 2009; Pascual et al, 2009; Sabeti and Gruol, 2008). Alcohol disruption of these processes likely underlies the fact that adolescent drinking leads to increased incidence of alcohol abuse and addiction in adulthood (Alaux-Cantin et al, 2012; Hingson et al, 2006; Maldonado-Devincci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%